Indirect Redox Transformations of Iron, Copper, and Chromium Catalyzed by Extremely Acidophilic Bacteria - Johnson, D. Barrie; Hedrich, Sabrina; Pakostova, Eva (Frontiers in Microbiology, 2017)
Experiments were carried out to examine redox transformations of copper and chromium by acidophilic bacteria (Acidithiobacillus, Leptospirillum and Acidiphilium), and also of iron (III) reduction by Acidithiobacillus spp. under aerobic conditions. Reduction of iron (III) was found with all five species of Acidithiobacillus tested, grown aerobically on elemental sulfur. Cultures maintained at pH 1.0 for protracted periods displayed increasing propensity for aerobic iron (III) reduction, which was observed in cell-free culture as well as those containing bacteria. At. caldus grown on hydrogen also reduced iron (III) under aerobic conditions, confirming that the unknown metabolite(s) responsible for iron (III) reduction were not (exclusively) sulfur intermediates. Reduction of copper (II) by aerobic cultures of sulfur-grown Acidithiobacillus spp. showed similar trends to iron (III) reduction in being more pronounced as culture pH declined, and occurring in both the presence and absence of cells. Cultures of Acidithiobacillus grown anaerobically on hydrogen only reduced copper (II) when iron (III) (which was also reduced) was also included; identical results were found with Acidiphilium cryptum grown micro-aerobically on glucose. Harvested biomass of hydrogen-grown At. ferridurans oxidised iron (II) but not copper (I), and copper (I) was only oxidised by growing cultures of Acidithiobacillus spp. when iron (II) was also included. The data confirmed that oxidation and reduction of copper were both mediated by acidophilic bacteria indirectly, via iron (II) and iron (III). No oxidation of chromium (III) by acidophilic bacteria was observed even when, in the case of Leptospirillum spp., the redox potential of oxidised cultures exceeded +900 mV. Cultures of At. ferridurans and A. cryptum reduced chromium (VI), though only when iron (III) was also present, confirming an indirect mechanism and contradicting an earlier report of direct chromium reduction by A. cryptum. Measurements of redox potentials of iron, copper and chromium couples in acidic, sulfate-containing liquors showed that these differed from situations where metals are not complexed by inorganic ligands, and supported the current observations of indirect copper oxido-reduction and chromium reduction mediated by acidophilic bacteria. The implications of these results for both industrial applications of acidophiles and for exobiology are discussed.